The role of business incubators in Saudi universities in supporting entrepreneurial thought in light of the knowledge economy and the requirements for its activation according to reference documents - Alanazi, Noof Atallah; Alanazi, Etaf Lahig; Alsalhani, Norah Obaid (Journal of Educational and Psychological Sciences, 2023)
The research aimed at identify the role of university business incubators in supporting entrepreneurial thought in light of the knowledge economy, through: reviewing the efforts of university business incubators in supporting entrepreneurial thought that target the initiatives of centers of creativity, innovation and entrepreneurship, then identifying the obstacles to the success of these efforts, and monitoring the proposed policies to enhance them. and improve it. The researcher used the descriptive analytical documentary method. Review the literature related to its variables; During a period of time, to introduce innovation and the efforts of Saudi universities in enhancing the role of business incubators in supporting entrepreneurial thought, entrepreneurship projects, innovation and creativity, a set of proposed policies were also monitored to support and enhance the role of university business incubators in this. The research reached a number of conclusions, including: that university business incubators have prominent efforts in supporting entrepreneurial thought, but they are still in the field of unsustainable production of knowledge, and have not moved on to transforming knowledge into entrepreneurial projects, and these efforts have not reached the role expected of them in incubating, nurturing, and achieving sustainability and competitiveness. He attributed This research examines a group of obstacles linked to each other through overlapping relative relationships, which make them influence and be affected by each other in a complementary manner. These obstacles are human, organizational, financial, societal and cognitive obstacles. In light of the research results, a number of recommendations were presented that would activate the role of business incubators in Saudi universities, including: The most important of which is increasing government and private funding for business incubators, providing training and qualification for human cadres working in business incubators, and enhancing cooperation between business incubators in Saudi universities.
Keywords: business incubators; entrepreneurship; knowledge economy; Saudi universities